Therapeutic approach to patients complaining of high blood pressure in a cardiological emergency room - Gus,Miguel (1999)
OBJECTIVE: To evaluate the management of patients complaining of high blood pressure (BP) in a cardiological emergency room. METHODS: Patients referred to the cardiological emergency room with the main complaint of high blood pressure were consecutively selected. The prescriptions and the choice of antihypertensive drugs were assessed. The classification of these patients as hypertensive emergencies or pseudoemergencies, according to the physician who provided initial care, was recorded. RESULTS: From a total of 858 patients presenting to the emergency room, 80 (9.3%) complained of high BP, and 61 (76.3%) received antihypertensive drugs. Sublingual nifedipine was the most commonly used drug (59%). One patient received intravenous medication, one patient was hospitalized and 6 patients (7.5%) were classified as hypertensive emergencies or pseudoemergencies. CONCLUSION: High BP could seldom be classified as a hypertensive emergency or pseudoemergency, even though it was a frequent complaint (9.3% of visits). Currently, the therapeutic approach is not recommended, even in specialized clinics.